Is binding decline the main source of the ageing effect on prospective memory? A ride in a virtual town. (1st January 2017) - Lecouvey, Grégory; Gonneaud, Julie; Piolino, Pascale; Madeleine, Sophie; Orriols, Eric; Fleury, Philippe; Eustache, Francis; Desgranges, Béatrice
ABSTRACT: Objective : This study was designed to improve our understanding of prospective memory (PM) changes in ageing, and to identify the cognitive correlates of PM decline, using a virtual environment, to provide a more realistic assessment than traditional laboratory tasks. Design : Thirty-five young and 29 older individuals exposed to a virtual town were asked to recall three event-based intentions with a strong link between prospective and retrospective components, three event-based intentions with a weak link, and three time-based intentions. They also underwent retrospective episodic memory, executive functions, binding in working memory, processing speed, and time estimation assessments. Results : Older individuals recalled fewer intentions than young adults. While age-related PM decline affected the recall of both prospective and retrospective components, the recall of the latter seemed more challenging for older individuals when the link was weak. This PM decline was linked to an age-related decline in the binding process in working memory, as well as in processing speed, executive functioning, and episodic memory, depending on the nature of intentions. Conclusion : PM appears to be sensitive to ageing, even when the device is thought to be ecological. This decline is particularly pronounced when controlled processes are needed.